Skip to content
Related Articles

Related Articles

Improve Article
Save Article
Like Article

Class 9 RD Sharma Solutions – Chapter 6 Factorisation of Polynomials- Exercise 6.4 | Set 1

  • Last Updated : 11 Feb, 2021

In each of the following, use factor theorem to find whether polynomial g(x) is a factor of polynomial f(x), or not(Question 1-7):

Question 1. f(x) = x3 – 6x2 + 11x – 6, g(x) = x – 3

Solution: 

Given: f(x) = x3 – 6x2 + 11x – 6, g(x) = x – 3

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

Here,



x – 3 = 0

x = 3 

To prove: g(x) is a factor of f(x), that is f(3) = 0 

On substituting the value of x in f(x), we get

 f(3) = 33 – 6 × 32 + 11 × 3 – 6

= 27 – (6 × 9) + 33 – 6

= 27 – 54 + 33 – 6

= 60 – 60

= 0 

Since, the result is 0, 

Hence, proved that g(x) is a factor of f(x).

Question 2. f(x) = 3x4 + 17x3 + 9x2 – 7x – 10, g(x) = x + 5

Solution: 

Given: f(x) = 3x4 + 17x3 + 9x2 – 7x – 10, g(x) = x + 5

Here,

x + 5 = 0

x = -5

To prove: g(x) is a factor of f(x), that is f(-5) = 0

On substituting the value of x in f(x), we get



f(-5) = 3(-5)4+ 17(-5)3+ 9(-5)2– 7(-5) – 10

= 3 × 625 + 17 × (-125) + 9 × 25 + 35 – 10

= 1875 – 2125 + 225 + 35 – 10

= 2135 – 2135

= 0 

Since, the result is 0, 

Hence, proved that g(x) is a factor of f(x).

Question 3. f(x) = x5 + 3x4 – x3 – 3x2 + 5x + 15, g(x) = x +  3

Solution: 

Given: f(x) = x5 + 3x4 – x3 – 3x2 + 5x + 15, g(x) = x + 3

Here,

x + 3 = 0 

x = -3

To prove: g(x) is a factor of f(x), that is f(-3) = 0

On substituting the value of x in f(x), we get

f(-3) = (-3)5 + 3(-3)4 – (-3)3 – 3(-3)2 + 5(-3) + 15

= -243 + 243 + 27 – 27 – 15 + 15

= 0

Since, the result is 0, 

Hence, proved that g(x) is a factor of f(x).

Question 4. f(x) = x3 – 6x2 – 19x + 84, g(x) = x – 7

Solution: 



Given: f(x) = x3 – 6x2 – 19x + 84, g(x) = x – 7

Here,

x – 7 = 0  

x = 7

To prove: g(x) is a factor of f(x), that is f(7) = 0

On substituting the value of x in f(x), we get

f(7) = 73 – 6 × 72 – 19 × 7 + 84     

= 343 – (6 × 49) – (19 × 7) + 84

= 343 – 294 – 133 + 84

= 427 – 427

= 0

Since, the result is 0, 

Hence, proved that g(x) is a factor of f(x).

Question 5. f(x) = 3x3 + x2 – 20x + 12, g(x) = 3x – 2

Solution: 

Given: f(x) = 3x3 + x2 – 20x + 12, g(x) = 3x – 2

Here,

3x – 2 = 0  

x = 2/3

To prove: g(x) is a factor of f(x), that is f(2/3) = 0

On substituting the value of x in f(x), we get

f(\frac23)=3(\frac23)^3+(\frac23)^2-20(\frac23)+12

= 3(\frac8{27})+\frac49-\frac{40}3+12

=\frac89+\frac49-\frac{40}3+12

= \frac{12}9-\frac{40}3+12

Taking L.C.M 

 = \frac{12-120+108}{9}

 =\frac{120-120}{9}

 = 0 

Since, the result is 0, 

Hence, proved that g(x) is a factor of f(x).



Question 6. f(x) = 2x3 – 9x2 + x + 13, g(x) = 3 – 2x

Solution: 

Given: f(x) = 2x3 – 9x2 + x + 13, g(x) = 3 – 2x

Here,

3 – 2x = 0  

x = 3/2

To prove: g(x) is a factor of f(x), that is f(3/2) = 0

On substituting the value of x in f(x), we get

f(\frac32)=2(\frac32)^3-9(\frac32)^2+(\frac32)+13

=2(\frac{27}8)-9(\frac94)+\frac34+13

=\frac{27}4-\frac{81}4 +\frac{3}{2}+12



=\frac{21-81+6+48}{4}

 = \frac{81-81}4

= 0 

Since, the result is 0, 

Hence, proved that g(x) is a factor of f(x).

Question 7. f(x) = x3 – 6x2 + 11x – 6, g(x) = x2 – 3x + 2

Solution: 

Given: f(x) = x3 – 6x2 + 11x – 6, g(x) = x2 – 3x + 2

Here,

x2 – 3x + 2 = 0  

On factorizing the above, we get

⇒ x2 – 3x + 2 = 0

⇒ x2 – 2x – x + 2 = 0

⇒ x(x – 2) – 1(x – 2)

⇒ (x – 1)(x – 2) are the factors 

To prove: g(x) is a factor of f(x), that is f(1) and f(2) should be 0

Let x = 1 

On substituting the value of x in f(x), we get

f(1) = 13 – 6 × 12 + 11 × 1 – 6

= 1 – 6 + 11 – 6

= 12 – 12

= 0 

Let x = 2

On substituting the value of x in f(x), we get

f(x) = 23 – 6 × 22 + 11 × 2 – 6 

= 8 – (6 × 4) + 22 – 6

= 8 – 24 +22 – 6

= 30 – 30

= 0

Since, the results are 0 g(x) is the factor of f(x)

Question 8. Show that (x – 2), (x + 3) and (x – 4) are the factors of x3 – 3x2 – 10x + 24

Solution: 



Given:

 f(x) = x3 – 3x2 – 10x + 24 

Factors given are (x – 2), (x + 3) and (x – 4)

To prove: g(x) is a factor of f(x), that is f(2), f(-3), f(4) should be 0

Here, x – 2 = 0

Let, x = 2

On substituting the value of x in f(x), we get

 f(2) = 23 – 3 × 22 – 10 × 2 + 24 

= 8 – (3 × 4) – 20 + 24

= 8 – 12 – 20 + 24

= 32 – 32

= 0 

Here, x + 3 = 0

Let, x = -3

On substituting the value of x in f(x), we get

f(-3) = (-3)3 – 3 × (-3)2 – 10 × (-3) + 24

= -27 -3(9) + 30 + 24

= -27- 27 + 30 + 24

= 54 – 54

= 0  

Here, x – 4 = 0

Let, x = 4

On substituting the value of x in f(x), we get

f(4) = (4)3 – 3 × (4)2 – 10 × (4) + 24

= 64 – 3(16) – 40 + 24

= 64 – 48 – 40 + 24

= 84 – 84

= 0  

Since, the results are 0, g(x) is the factor of f(x)

Question 9. Show that (x + 4), (x – 3) and (x – 7) are the factors of x3 – 6x2 – 19x + 84

Solution: 

Given:

f(x) = x3 – 6x2– 19x + 84

Factors given are (x + 4), (x – 3) and (x – 7)

To prove: g(x) is a factor of f(x), that is f(4), f(3), f(-7) should be 0

Here, x + 4 = 0

Let, x = -4

On substituting the value of x in f(x), we get

f(-4) = (-4)3 – 6(-4)2 – 19(-4) + 84

= -64 – (6 × 16) – 19 × (-4) + 84

= -64 – 96 + 76 + 84

= 160 – 160

= 0

Here, x – 3 = 0

Let, x = 3

On substituting the value of x in f(x), we get

f(3) = (3)3 – 6(3)2 – 19(3) + 84

= 27 – 6(9) – 19 × 3 + 84

= 27 – 54 – 57 + 84

= 111 – 111

= 0  

Here, x – 7 = 0

Let, x = 7

On substituting the value of x in f(x), we get

f(7) = (7)3 – 6(7)2 – 19(7) + 84

= 343 – 6(49) – 19 × 7 + 84

= 343 – 294 – 133 + 84

= 427 – 427

= 0  

Since, the results are 0, g(x) is the factor of f(x)

Question 10. For what value of a is (x – 5) a factor of x3 – 3x2 + ax – 10    

Solution: 



Here, f(x) = x3 – 3x2 + ax – 10

By factor theorem 

If (x – 5) is the factor of f(x) then, f(5) = 0 

⇒ x – 5 = 0

⇒ x = 5

On substituting the value of x in f(x), we get

f(5) = 53 – 3 × 52 + a × 5 – 10

= 125 – (3 × 25) + 5a -10

= 125 – 75 + 5a – 10

= 5a + 40

Equate f(5) to zero

f(5) = 0 

⇒ 5a + 40 = 0

⇒ 5a = -40

⇒ a = -40/5

⇒ a = -8

When a = -8, then (x – 5) will be factor of f(x)

Question 11. Find the value of such that (x – 4) is a factor of  5x3 – 7x2 – ax – 28    

Solution: 

Given: f(x) = 5x3– 7x2– ax – 28

Using factor theorem

(x – 4) is the factor of f(x), then f(4) = 0 

⇒ x – 4 = 0

⇒ x = 4

On substituting the value of x in f(x), we get

f(4) = 5(4)3 – 7(4)2 – a × 4 – 28

= 5(64) – 7(16) – 4a – 28

= 320 – 112 – 4a – 28

= 180 – 4a

Equate f(4) to zero, to find a

f(4) = 0

⇒ 180 – 4a = 0 

⇒ a = 180/4

⇒ a = 45     

When a = 45, then (x – 4) will be factor of f(x)

Question 12. Find the value of a, if (x + 2) is a factor of 4x4 + 2x3 – 3x2 + 8x + 5a 

Solution: 

Given: f(x) = 4x4+ 2x3– 3x2+ 8x + 5a 

Using factor theorem 

If (x + 2) is the factor of f(x), then f(-2) should be zero

⇒ x + 2 =0 

⇒ x = -2

On substituting the value of x in f(x), we get

f(-2) = 4(-2)4+ 2(-2)3– 3(-2)2+ 8(-2) + 5a 

= 4(16) + 2 (-8) – 3(4) – 16 + 5a

= 64 – 16 – 12 -16 + 5a

= 5a + 20

Equate f(-2) to 0 

f(-2) = 4(-2)2+ 2(-2)3– 3(-2)2+ 8(-2) + 5a 

= 4(16) + 2(-8) – 3(4) – 16 + 5a

= 64 – 16 – 12 – 16 + 5a

= 5a + 20

Equate f(-2) to 0

f(-2) = 0

⇒ 5a + 20 = 0

⇒ 5a = – 20

⇒ a = -4

When a = -4, then (x + 2) is the factor of f(x)




My Personal Notes arrow_drop_up
Recommended Articles
Page :